139k views
2 votes
Solve the equation. Check your solution. - 6y + 5 = 29y - 2​

User Ikuko
by
5.3k points

2 Answers

4 votes

Answer:

y=0.20

Explanation:

-6y+5=29y-2 Carry the -6 over to the 29.

5=35y-2 Carry the -2 over to the 5.

7=35y

y=0.20

CHECK: -6(0.20)+5=29(0.20)-2

-1.2+5= 5.8-2

3.8=3.8

If you have any questions feel free to ask

User Andrei Cozma
by
6.2k points
4 votes

Answer:

y = 0.2

Explanation:

Simplifying

-6y + 5 = 29y + -2

Reorder the terms:

5 + -6y = 29y + -2

Reorder the terms:

5 + -6y = -2 + 29y

Solving

5 + -6y = -2 + 29y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-29y' to each side of the equation.

5 + -6y + -29y = -2 + 29y + -29y

Combine like terms: -6y + -29y = -35y

5 + -35y = -2 + 29y + -29y

Combine like terms: 29y + -29y = 0

5 + -35y = -2 + 0

5 + -35y = -2

Add '-5' to each side of the equation.

5 + -5 + -35y = -2 + -5

Combine like terms: 5 + -5 = 0

0 + -35y = -2 + -5

-35y = -2 + -5

Combine like terms: -2 + -5 = -7

-35y = -7

Divide each side by '-35'.

y = 0.2

Simplifying

y = 0.2

User Daniel Mana
by
5.5k points